A study on machining of binder-less polycrystalline diamond by femtosecond pulsed laser for fabrication of micro milling tools. Issue 1 (2016) - Ogawa, Yoshinori; Ota, Michiharu; Nakamoto, Kazuo; Fukaya, Tomohiro; Russell, Marc; Zohdi, Tarek I.; Yamazaki, Kazuo; Aoyama, Hideki
Abstract: Since binder-less polycrystalline diamond (BLPCD) has no macro cleavage planes and highest hardness, it is desirable material for micro milling tools. However, fabricating micro tools made of BLPCD by conventional method such as grinding is very time consuming due to its extremely high hardness. This paper describes the successful results obtained in our recent study on productive machining of BLPCD using femtosecond-pulsed laser (FSPL). The ablation effect of BLPCD by FSPL has been studied by conducting a series of experiments. Also, the predictability of ablation effect of FSPL when machining BLPCD has been evaluated by introducing numerical analysis model.